Hover performance predictions of coaxial rotor configurations using the updated cmtsvt multirotor inflow model - Guner, F. (My University, 2022)
This paper uses the combined momentum theory and simple vortex theory (CMTSVT) multirotor inflow model for hover performance predictions of coaxial rotor configurations. The CMTSVT inflow model is updated with the wake contraction and decay functions, and their effects on performance predictions are discussed. For comparison, wind tunnel measurements available in the literature are used to study the effects of loading changes at the fixed axial separation distance and different axial separation distances at fixed loading settings. Apart from the figure of merit, power, and thrust sharing ratio predictions, factors such as the interference loss and rotor-rotor influence loss are determined to identify rotor-rotor interaction effects on the performance. Furthermore, the total, self, interference uniform inflow components along with the lower rotor inflow distributions plots are provided for further insight. It has been shown that additions of the wake contraction and decay functions tremendously improve the predictions of the CMTSVT inflow model. With additions of these real-flow effects, the CMTSVT inflow model can capture the effects of rotor-rotor interactions for different loading settings and axial separation distances.